Electric flocculation equipment for treating wastewater - MA CHENGLING; SHI XINGANG (2025)
The invention discloses electric flocculation equipment for wastewater treatment, and particularly relates to the technical field of wastewater treatment equipment.The electric flocculation equipment comprises a shell, a supporting frame is fixedly connected to the left portion of the lower end of the shell, supporting legs are fixedly connected to the front side and the rear side of the right portion of the lower end of the shell, and an inner container is fixedly connected to the inner surface of the shell; a concave plate is fixedly connected to the upper side of the middle of the left end of the shell and the upper side of the middle of the right end of the shell jointly, an aeration pump is fixedly connected to the left side of the upper end of the concave plate, an aeration assembly is arranged in an inner cavity of the inner container, an adjusting assembly is slidably installed at the rear end of the shell, and a sludge receiving assembly is fixedly installed at the lower end of the inner container. A